KAIDAH USHULIYYAH MANTHUK DAN MAFHUM DALAM PROSES ISTIMBATH HUKUM THARIQOH MUTAKALLIMIN DAN FUQOHA - ardi, sahibul (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Usul Fiqh is a science related to sharia which is 'Ijmali or kulli, a method of imposing and the conditions for establishing a law that must be fulfilled by a mujtahid. Istinbat al-Ahkam from the texts of the Qur'an and Hadith can be reached in two ways, namely the lughawiyah (usuliyyah) principles approach; and the tasyri'iyyah rules approach. Kaidah (rules) mean a system in general. The word usuliyyah means principal and comprehensive. It means that Usuliyyah does not only apply to a certain law. The rule of usuliyyah is a general rule that is used to set or establish a law. The ushuliyyah rule is related to pronunciation and dalalah or more related in to language (Arabic). There are many discussions related to language, including Manthuq and mafhum, wadih and mubham, 'am and khas, amr and nahi, mutlaq and muqayyad and others. This paper will explore the usuliyyah rules of Manthuq and mafhum from two groups, namely Mutakallimin and Fuqoha in a normative descriptive side with a qualitative approach. The results of the study show that there are differences in Dilalah Alfadz and its hujjah between the Mutakalillimin and Fuqoha people in the context of taking texts as a source of law.